Effect of Mechanical Compression and Hydrostatic Pressure on the Molecular Mobility of Poly(lactic acid). Issue 1 (July 2014) - Bouthegourd, Emilie; Esposito, Antonella; Saiter, Allisson; Saiter, Jean‐Marc
Summary The molecular mobility of an organic glass (PLA with 4.3% of D‐lactic acid content) was investigated by calculating the size of the Cooperative Rearranging Regions (CRR) at its glass transition. The samples were exposed to different external constraints – namely a large deformation by mechanical compression at T < Tg (prior to measurement) or different hydrostatic pressures (during the measurement). The measurements were performed by Differential Scanning Calorimetry (DSC) techniques: standard, temperature modulated (TM‐DSC) and high pressure (HP‐DSC). It was shown that mechanical deformations above the elastic limit increase the CRR size and shift the Tg value to higher temperatures, but have no effect on the value of ΔCp(Tg). On the other hand, increasing the hydrostatic pressure during the measurement (1 to 100 bar) decreases the CRR size, slightly influences Tg and does not change the value of ΔCp(Tg).